AAGBS Annual Report 2021: at a glance (Doctor of Philosophy) - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2021)
This Doctor of Philosophy (Business Management) (PhD) program brings together academia and practitioners driven by research that is academic and industry related. Students will be guided and supervised by dedicated and experienced faculty members.